Recycled wastewater and product choice: Does it make a difference if and when you taste it?. (March 2016) - Hatton MacDonald, Darla; Rose, John M.; Lease, Haidee J.; Cox, David N.
Highlights: Participants "just answering a survey" may overstate acceptability. Experience of product results in relative differences in error variance & preferences. Participants prefer tap water throughout production relative to recycled water contact. Willingness to pay for tap water is 3 times higher if choices consequential. Abstract: With water security issues looming large for much of the world's population, efficient use of water will become increasingly important. One solution is recycling wastewater however consumer acceptability is uncertain with the potential for rejection. People may support wastewater recycling conceptually but reject products containing recycled water due to the "yuck" factor. This simple problem presented an opportunity to compare different experimental approaches emerging from different literatures. This paper reports on an experiment which utilises meat products purported to be manufactured with or containing recycled production wastewater to explore choice behaviour. Participants ( n = 203 adult consumers of minced beef products) were randomly assigned into two conditions, a Binding Condition (told they would be eating four random selections of their next choices) and an Experience Condition (asked to taste four meatball samples prior to completing their next lot of choices). Statistically significant preference and scale differences between the pre-and post intervention were observed suggesting that participants may initially under-estimate their acceptance of a product with a negative attribute when they believe they are just answering a survey. One explanation of the differences among conditions is that participants experience a degree of anticipatory dread if told they will be eating their next choices in a survey compared with just answering a survey or experiencing the product prior to making choices. Results suggest that any investment in recycling will need to be justified on the basis of avoided waste charges and/or reductions in input costs as consumers are not willing to pay a premium to conserve water.